Adventures in 1,1-Diphenylacetone Dianion Chemistry - Langer, Peter (Synlett, 2023)
The present personalized account highlights reactions of the dianion of 1,1-diphenylacetone and its applications. From a study directed towards the regioselectivity of such reactions a new allene synthesis via allene dianions was found by serendipity. In addition, reactions of allene dianions with various electrophiles have been studied.1 Introduction2 Cyclizations of the Dianion of 1,1-Diphenylacetone2.1 Reaction with Bis(cyclopentadienyl)zirconium Dichloride2.1 Reactions with Dichlorosilanes2.1 Reactions with Difluorosilanes2.1 Reactions with Ketones and Dielectrophiles3 Regioselectivity of Dianion Reactions4 Allene Dianions from Silyl Enol Ethers5 Scope of the Reactions of Allene Dianions6 Reactions of Allene Dianions with Ketones7 Reactions of Allene Dianions with Nitriles8 Conclusions
Keywords: allenes; cyclizations; dianions; silicon; silyl enol ethers